If f(x)=x^2-3 and g(x)=5x-2, evaluate f(-1)-g(2)?
To evaluate expressions like `f(-1)-g(2)` , we need to remember that a function evaluation is just a number, and that two numbers may be subtracted like in that expression. This means that each function needs to be evaluated separately, then subtracted.
`f(-1)-g(2)` sub -1 in f(x) and 2 in g(x)
`=((-1)^2-3)-(5(2)-2)` now evaluate, being careful with order of operations
`=(1-3)-(10-2)` continue to work from the inside out
The expression evaluates to -10.